A cenografia e a constituição do ethos no discurso literário produzido por Clarice Lispector - Souza, Simone Maria Verdum (2021)
This dissertation is inserted in the theoretical and methodological postulates of the French Discourse Analysis and is examined The scenography and the constitution of ethos in the literary discourse produced by Clarice Lispector. The theme is relevant because, through literary discourse and the enunciative-discursive perspective, we observe the condition of submission in which women, especially those who lived through the mid-twentieth century, were subjected. The constituted corpus has allusions to the feminine behavior, desired and taught, so that the woman was responsible for domestic chores and male subservience. This can be perceived by the unveiling of the topical and non-topical units of discourse, which have an extrinsic representation to the literary enunciation; therefore, the dialogue between Literature, History, and Sociology also serves as recognition of discursive marks. For our analysis, the concepts treated by Maingueneau, such as Literary Discourse, scenography, and discursive ethos, are used as a basis. The proposed analysis is based on a theoreticalmethodological procedure in which scenography, instituted by topical and non-topical units, reveal, in the selected literary discourse, a submissive and repressed female ethos, which discursively emerges in the selected tales of Laços de Família, here apprehended as discourses